Relationship between platelet indices and lipidemias: A cross-sectional study at Karachi - Khan, Sikandar Hayat; Ahmad, Syed Azhar (Journal of Postgraduate Medical Institute, 2014)
Objective: To compare platelet indices among patients with low and high levels of cholesterolemia and triglyceridemia Methodology: This cross-sectional study was conducted from January 2011to May 2012 at the departments of pathology, PNS Rahat and Baqai medical and dental university, Karachi. A total of 867 subjects presenting for estimation of fasting triglycerides and total cholesterol were selected after excluding patients receiving anti-platelet or lipid medication, pregnancy, acute infectious disorders. They were interviewed, examined and sampled for measurement of total cholesterol, triglycerides and platelet indices including total platelet count, mean platelet volume (MPV), platelet distribution width (PDW) and platecrit (PCT). Results: The results of platelet count and mean platelet volume were found tobe significantly different among subjects with normal cholesterolemia (<5.2mmol/L), borderline raised cholesterol group (5.2-6.3 mmol/L) and hypercholesterolemia (>6.3 mmol/L); however, post-hoc comparison did not show any significant difference between all groups. Using age as a variable and segregating total cholesterol results into 7 groups, starting from very low cholesterol values (<4.0 mmol/L) to highest (>6.5 mmol/L), in a univariate general linear model, higher mean platelet volume were observed at the extremes ofcholesterolemia groups [p=0.039]. A similar trend was observed for platelet count after adjusting for age, where low levels of platelet levels were associated with hypocholesterolemia and hypercholesterolemia (p=0.021). Conclusion: Higher MPV and low total platelet counts were associated with the observed extremes of cholesterol range. No significant differences were observed for platelet indices across various groups formulated based upon fasting triglycerides.